Stressors and well-being in Low SES Malaysian adolescents: the role of resilience resources - Noor, Noraini M.; Alwi, Azlin (Wiley Publishing Asia Pty Ltd with the Asian Association of Social Psychology and the Japanese Group Dynamics Association, 2013)
The present study examined the relationship between stressors, resilience resources and well-being in adolescents. The specific aims were (i) to differentiate between resilient and non-resilient adolescents in terms of their resilience resources, and (ii) to examine the role of resilience resources on the relationship between stressors and well-being. In a sample of 197 adolescents aged 12-16 years (mean = 13.77, sd = 1.49), results of the k-mean clustering technique identified 37.5% of the adolescents as resilient (high stressor, high well-being), 31.0% as maladjusted (high stressor, low well-being), and the rest, adapted (low stressor, high well-being). Resilient adolescents were found to have significantly higher scores on all the identified resilience resources (personality, mother-child communication, social support, school coherence and teacher support) compared to the non-resilient maladjusted group. Results of the structural equation modelling also showed these resilience resources to act both as mediator and moderator in the relationship between stressors and well-being. These findings are discussed with respect to the current literature on resilience and well-being.